Evaluation methods for assessing effectiveness of in situ remediation of soil and sediment contaminated with organic pollutants and heavy metals. (August 2017) - Song, Biao; Zeng, Guangming; Gong, Jilai; Liang, Jie; Xu, Piao; Liu, Zhifeng; Zhang, Yi; Zhang, Chen; Cheng, Min; Liu, Yang; Ye, Shujing; Yi, Huan; et al.
Abstract: Soil and sediment contamination has become a critical issue worldwide due to its great harm to the ecological environment and public health. In recent years, many remediation technologies including physical, chemical, biological, and combined methods have been proposed and adopted for the purpose of solving the problems of soil and sediment contamination. However, current research on evaluation methods for assessing these remediation technologies is scattered and lacks valid and integrated evaluation methods for assessing the remediation effectiveness. This paper provides a comprehensive review with an environmental perspective on the evaluation methods for assessing the effectiveness of in situ remediation of soil and sediment contaminated with organic pollutants and heavy metals. The review systematically summarizes recent exploration and attempts of the remediation effectiveness assessment based on the content of pollutants, soil and sediment characteristics, and ecological risks. Moreover, limitations and future research needs of the practical assessment are discussed. These limitations are not conducive to the implementation of the abatement and control programs for soil and sediment contamination. Therefore, more attention should be paid to the evaluation methods for assessing the remediation effectiveness while developing new in situ remediation technologies in future research. Graphical abstract: Highlights: Methods for in situ remediation of contaminated soil and sediment are outlined. Recent assessments of the remediation effectiveness are systematically summarized. Evaluation principles involved in the assessments are discussed. The limitations and future research needs are suggested.